(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The leather industry is one of India’s oldest industrial industries and plays a significant role in the Indian economy. It employs over 2.5 million people in the country and generates roughly 5 million in annual revenue. Because of its abundant raw materials, India is one of the best places in the world to invest in the leather business. Therefore, it is essential to follow the development of India’s leather industry. This article is It was the first attempt to analyze the growth and composition of the workforce in the Indian leather industry using the annual compound interest growth rate. Second, clarify the relationship between the growth of the Indian leather industry and employment, wages and net value added (NVA). Finally, we used regression analysis to analyze the impact of labor productivity on wage setting. The individual NIC codes (151 and 152) were chosen to draw inferences between these 2 codes to give an overview of the leather industry.